Management of Urinary Incontinence with Kegel Gymnastics in Elderly Patients with Urine Elimination Disorders - Lisdahayati Lisdahayati; Gunardi Pome; Zanzibar Zanzibar; Saprianto Saprianto; Zeta Viona (School of Health Sciences Al-Ma'arif, 2025)
Urinary incontinence is a common issue among the elderly caused by pelvic floor muscle weakness and significantly impacts their quality of life. Objective: This study aims to describe the implementation of Kegel exercises to reduce urinary incontinence symptoms in elderly patients at the Tanjung Agung Health Center. Methods: This descriptive study employed a case study approach involving two elderly patients with urinary incontinence. The intervention included education, demonstration, and evaluation of Kegel exercises conducted over four weeks. Results: Both patients showed a significant reduction in urination frequency, from 14-16 times per day to 5-6 times per day. They also reported improved urinary control and a better quality of life. Conclusion: Kegel exercises are an effective intervention to reduce urinary incontinence symptoms in the elderly. Recommendation: Nurses are encouraged to integrate Kegel exercises into geriatric nursing management with family support to enhance therapy outcomes.